Lessons Learned From a Prospective Observational Study of U.S. Marine Recruits During a Supervised Quarantine, Spring‒Fall 2020 - Andrew G. Letizia, MD; Carl W. Goforth, PhD; Yongchao Ge, PhD; Michael S. Termini, MD; Megan A. Schilling, PhD; Victor A. Sugiharto, PhD; Hua Wei Chen, PhD; Irene Ramos, PhD; Stuart C. Sealfon, MD (Elsevier, 2022)
Introduction: Quarantining is commonly used to mitigate the spread of SARS-CoV-2. However, questions remain regarding what specific interventions are most effective. Methods: After a 2-week home quarantine, U.S. Marine Corps recruits underwent a supervised 2-week quarantine at a hotel from August 11 to September 21, 2020. All recruits were assessed for symptoms through oral questioning and had their temperatures checked daily. Study participants answered a written clinical questionnaire and were tested for SARS-CoV-2 by polymerase chain reaction shortly after arrival in quarantine and on Days 7 and 14. The results were compared with those of a previously reported Marine-supervised quarantine at a college campus from May until July 2020 utilizing the same study, laboratory, and statistical procedures. Results: A total of 1,401 of 1,514 eligible recruits (92.5%) enrolled in the study, 93.1% of whom were male. At the time of enrollment, 12 of 1,401 (0.9%) participants were polymerase chain reaction positive for SARS-CoV-2, 9 of 1,376 (0.7%) were positive on Day 7, and 1 of 1,358 (0.1%) was positive on Day 14. Only 12 of 22 (54.5%) participants endorsed any symptoms on a study questionnaire, and none of the participants had an elevated temperature or endorsed symptoms during daily screening for SARS-CoV-2. Participation rate (92%) was much greater than the approximately 58.8% (1,848 of 3,143) rate observed in the previous Marine-supervised college campus quarantine, suggesting the changing attitudes of recruits during the pandemic (p<0.001). Approximately 1% of participants were quantitative polymerase chain reaction positive after self-quarantine in both studies. Conclusions: Key findings include the shifting attitudes of young adults during the pandemic, the limitations of self-quarantine, and the ineffectiveness of daily temperature and symptom screening to identify SARS-CoV-2‒positive recruits.